Essential tremor patients experience significant burden beyond tremor: A systematic literature review - Gerbasi, Margaret E.; Nambiar, Shruti; Reed, Spencer; Hennegan, Kalin; Hadker, Nandini; Eldar-Lissai, Adi; Cosentino, Stephanie (Frontiers in Neurology, 2022)
Background: Essential tremor (ET) is among the most common movement disorders in adults. While ET is diagnosed and primarily characterized by the presence of tremor, it can also impact cognition, sleep, mood, and motor functioning more broadly. The manifestations of ET have various consequences, including difficulty with activities of daily living (ADL), embarrassment, and overall decline in health-related quality of life, which have not been fully explored in prior studies. Objective: We performed a systematic literature review to comprehensively characterize the burden experienced by patients with ET from the clinical and humanistic perspectives, focusing on outcomes beyond tremor. Methods: This systematic literature review followed Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Searches in PubMed, Embase, and Cochrane Library identified original, observational studies of the clinical and humanistic burden in adult patients with ET published in English between 2010-2020. Studies assessing epidemiology, treatment patterns, or disease management were excluded. Search results were screened according to pre-determined eligibility criteria. Data from included studies were collected, independently verified, and qualitatively synthesized. Results: Following the screening of 2,302 records and 145 full-text articles, 39 studies were identified. There was significant heterogeneity in study designs, statistical approaches, and patient cohorts across the included studies. Patients with ET in these studies exhibited more severe disabilities and reduced independence compared to healthy individuals, and they often struggled to perform ADL and relied on caregivers for physical and emotional support. Patients also experienced various issues with movement and balance, increased risk of falls, depression, anxiety, poor sleep quality, and psychosocial consequences including embarrassment, apathy, and enfeeblement. Conclusion: A systematic literature review of non-tremor manifestations and/or consequences of ET identified far-reaching negative impacts on patients’ ability to function independently and revealed accompanying psychosocial effects, including social fear and embarrassment. The reduced function and psychosocial deficits observed in patients with ET result in significant clinical and humanistic burdens, decreasing quality of life. Future studies should evaluate this condition beyond the tremor itself to provide an improved understanding of the multi-dimensional burden of the disease, thereby highlighting the need to diagnose and appropriately manage patients with ET.